2005
DOI: 10.1002/hipo.20106
|View full text |Cite
|
Sign up to set email alerts
|

Medial prefrontal cortex cells show dynamic modulation with the hippocampal theta rhythm dependent on behavior

Abstract: Both the hippocampus and the medial prefrontal cortex are essential for successful performance in learning- and memory-related tasks. Within the hippocampus the theta rhythm plays an integral role in the timing of action potentials of hippocampal neurons responding to elements of any given task. Medial prefrontal cortex (mPFC) neurons display firing rate changes to specific facets of behavioral tasks (Jung et al., 1998. Cereb Cortex 8:437--450). We recorded units in the mPFC and field potentials in the hippoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

27
243
1
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 271 publications
(276 citation statements)
references
References 39 publications
(42 reference statements)
27
243
1
1
Order By: Relevance
“…These data are consistent with previous examinations of communication between the medial prefrontal cortex and hippocampus of rodents (Siapas et al, 2005;Wilson, 2005a, 2005b;Hyman et al, 2005Hyman et al, , 2010Sirota et al, 2008;Hartwich et al, 2009;Young and McNaughton, 2009;Adhikari et al, 2010;Benchenane et al, 2010; also reviewed by Colgin, 2011). Most research in this area has looked at neural activity correlations between the dorsal hippocampus and the prelimbic cortex, located just dorsal to the IL, and patterns have been linked to cognitive variables such as working memory (Jones and Wilson, 2005b;Hyman et al, 2005) and expectation-based decision-making (Benchenane et al, 2010). Meanwhile, coherence between the VH and the prelimbic cortex has been linked to anxiety (Adhikari et al, 2010).…”
Section: Discussionsupporting
confidence: 92%
“…These data are consistent with previous examinations of communication between the medial prefrontal cortex and hippocampus of rodents (Siapas et al, 2005;Wilson, 2005a, 2005b;Hyman et al, 2005Hyman et al, , 2010Sirota et al, 2008;Hartwich et al, 2009;Young and McNaughton, 2009;Adhikari et al, 2010;Benchenane et al, 2010; also reviewed by Colgin, 2011). Most research in this area has looked at neural activity correlations between the dorsal hippocampus and the prelimbic cortex, located just dorsal to the IL, and patterns have been linked to cognitive variables such as working memory (Jones and Wilson, 2005b;Hyman et al, 2005) and expectation-based decision-making (Benchenane et al, 2010). Meanwhile, coherence between the VH and the prelimbic cortex has been linked to anxiety (Adhikari et al, 2010).…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with this view, PFC neurons exhibit context-dependent anticipatory neural codes for reward information (Pratt and Mizumori, 2001). Also, PFC neural signaling has been found to be conditionally linked to hippocampal output since PFC cell firing can become phase locked to CA1 hippocampal theta rhythms and precession (Hyman et al, 2005;Jones and Wilson, 2005). The entrained PFC neurons tended to be ones whose firing is correlated with specific behavioral acts (Hyman et al, 2005).…”
Section: Retrosplenial (Parietal) Cortex-hippocampal Interactionsmentioning
confidence: 81%
“…Also, PFC neural signaling has been found to be conditionally linked to hippocampal output since PFC cell firing can become phase locked to CA1 hippocampal theta rhythms and precession (Hyman et al, 2005;Jones and Wilson, 2005). The entrained PFC neurons tended to be ones whose firing is correlated with specific behavioral acts (Hyman et al, 2005). Furthermore, Hyman et al showed that testing subjects in different rooms caused some PFC neurons to change the degree to which they were entrained to the hippocampal theta rhythm, suggesting that the degree to which PFC is functionally connected to HPC was dependent on the stability of spatial context information…”
Section: Retrosplenial (Parietal) Cortex-hippocampal Interactionsmentioning
confidence: 99%
“…Additionally, hippocampal theta may be important for organizing interactions between disparate brain regions. Neurons in multiple brain regions, including prefrontal cortex, are phase-locked to the hippocampal theta rhythm (54)(55)(56), and the amplitude of locally generated gamma-band (30-140 Hz) oscillations is also modulated by hippocampal theta phase (55,57,58). This latter phenomenon may be particularly important for memory, because gamma synchrony within and between MTL regions is enhanced during successful memory task performance (18,59,60).…”
Section: Discussionmentioning
confidence: 99%